PERAN LOWBALLING DALAM MENGINTERVENING PENGARUH KOMPLEKSITAS DAN INDEPENDENSI TERHADAP KUALITAS AUDIT - Mochamad Fajar Yulianto (2021)
This research is using quantitative study aimed to see whether lowballing has a role as intervening for the influence of complexity and independency on audit quality. This study uses 57 auditors from 24 CPA's firm throughout Jakarta region as samples. Sample selection in this study uses purposively, with criteria for auditors with a level of experience above one year and have been involved in establishing initial engagements with clients. Hypothesis testing in this study uses path analysis by measuring the direct and indirect effects of each independent variable on the dependent variable using the SmartPLS tool with a significant level of 5% (0,05). The results of these tests obtained that (1) there is a positive and significant effect of complexity on audit quality, (2) there is no influence of complexity on audit quality through lowballing, (3) there is a positive and significant effect of independency on audit quality, (4) there is no influence of independency on audit quality through lowballing, and (5) there is no influence of lowballing on audit quality.